Hepcidin regulation by innate immune and infectious stimuli - Armitage, A; Eddowes, L; Gileadi, U; Cole, S; Spottiswoode, N; Selvakumar, T; Ho, L; Townsend, A; Drakesmith, H (2011)
Hepcidin controls the levels and distribution of iron, an element whose availability can influence the outcome of infections. We investigated hepcidin regulation by infection-associated cytokines, pathogen-derived molecules, and whole pathogens in vitro and in vivo. We found that IL-22, an effector cytokine implicated in responses to extracellular infections, caused IL-6-independent hepcidin upregulation in human hepatoma cells, suggesting it might represent an additional inflammatory hepcidin agonist. Like IL-6, IL-22 caused phosphorylation of STAT3 and synergized with BMP6 potentiating hepcidin induction. In human leukocytes, IL-6 caused potent, transient hepcidin up-regulation that was augmented by TGF-β1. Pathogen-derived TLR agonists also stimulated hepcidin, most notably the TLR5 agonist flagellin in an IL-6- dependent manner. In contrast, leukocyte hepcidin induction by heat-killed Candida albicans hyphae was IL-6-independent, but partially TGF-β- dependent. In a murine acute systemic candidiasis model, C albicans strongly stimulated hepcidin, accompanied by a major reduction in transferrin saturation. Similarly, hepcidin was up-regulated with concomitant lowering of serum iron during acute murine Influenza A/PR/8/34 virus (H1N1) infection. This intracellular pathogen also stimulated hepcidin expression in leukocytes and hepatoma cells. Together, these results indicate that hepcidin induction represents a component of the innate immune response to acute infection, with the potential to affect disease pathogenesis. © 2011 by The American Society of Hematology.